2000
DOI: 10.1046/j.1365-2567.2000.00990.x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of merosin (laminin 2) with very late activation antigen‐6 is necessary for the survival of CD4+ CD8+ immature thymocytes

Abstract: SUMMARYThe laminin a2-chain is a component of merosin, a member of the laminin family molecules, which is mainly expressed in the basement membranes of striated muscle. It is known that laminin a2 gene (lama2) null mutant mice (dy 3k /dy 3k ) exhibit congenital muscular dystrophy (CMD). Because the laminin a2-chain is also expressed in the thymus, the role of merosin in the thymus was examined. In association with the onset of muscular dystrophy, CD4+ CD8 + double-positive (DP) thymocytes disappear by apoptoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 36 publications
0
19
0
1
Order By: Relevance
“…Lack of α2 laminin impairs thymus development by reducing the amount of T cell progenitors, especially DP cells (Iwao et al 2000, Magner et al 2000. In vitro, LM-211 supports the survival of thymocytes (Iwao et al 2000). Laminins appear to have significant roles in the migration and inflammation of immune cells.…”
Section: Immune Systemmentioning
confidence: 98%
See 1 more Smart Citation
“…Lack of α2 laminin impairs thymus development by reducing the amount of T cell progenitors, especially DP cells (Iwao et al 2000, Magner et al 2000. In vitro, LM-211 supports the survival of thymocytes (Iwao et al 2000). Laminins appear to have significant roles in the migration and inflammation of immune cells.…”
Section: Immune Systemmentioning
confidence: 98%
“…In vitro, DN cells adhere strongly to α5 laminins, unlike DP cells, which reside within the cortex (Kutlesa et al 2002). Lack of α2 laminin impairs thymus development by reducing the amount of T cell progenitors, especially DP cells (Iwao et al 2000, Magner et al 2000. In vitro, LM-211 supports the survival of thymocytes (Iwao et al 2000).…”
Section: Immune Systemmentioning
confidence: 99%
“…In vitro , laminin 211 isolated from placenta favors the proliferation of anti-CD3-activated thymocytes via the integrins α3β1 and α6β1 [58]. This laminin isoform seems to regulate apoptosis as an increased number of apoptotic thymocytes has been observed in the thymic capsular and subcapsular regions in dy/dy mice [57] and increased apopototic cell death of the double-positive thymocytes in laminin α2-chain null mutant mice dy3k/dy3k [59]. The absence of laminin 211 has no effect on the apoptosis of mature single-positive thymocytes.…”
Section: Laminins and Immune System Interactionsmentioning
confidence: 99%
“…Studies with these tools have demonstrated a characteristic distribution of laminin isoforms in thymus and participation of ␣2-, ␣3-, and ␣5-laminins in adhesion, migration, proliferation, survival, and/or development of thymocytes and T cell malignancies [20,[25][26][27][28][29][30][31]. Moreover, adhesion and migration of neoplastic lymphocytes have been found to be promoted by ␣4-and ␣5-laminins [32,33].…”
Section: Introductionmentioning
confidence: 99%